2012
DOI: 10.1155/2012/436537
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Forest Biomass Estimation with Landsat and LiDAR Data and Uncertainty Analysis of the Estimates

Abstract: Landsat Thematic mapper (TM) image has long been the dominate data source, and recently LiDAR has offered an important new structural data stream for forest biomass estimations. On the other hand, forest biomass uncertainty analysis research has only recently obtained sufficient attention due to the difficulty in collecting reference data. This paper provides a brief overview of current forest biomass estimation methods using both TM and LiDAR data. A case study is then presented that demonstrates the forest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
156
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 87 publications
(135 reference statements)
5
156
0
9
Order By: Relevance
“…Estimating and mapping forest biomass/carbon stocks become essential for greenhouse gas inventories, global carbon cycle, and climate change modeling [1][2][3]. Various methods such as process models and remote sensing-based approaches have been developed and used [4][5][6][7]. The process models-based methods do not generate spatially explicit predictions and often lead to a large amount of uncertainty for specific sites, partly because too many variables and input parameters are required to run the models and partly because different source data such as climate and soil data have very coarse spatial resolutions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating and mapping forest biomass/carbon stocks become essential for greenhouse gas inventories, global carbon cycle, and climate change modeling [1][2][3]. Various methods such as process models and remote sensing-based approaches have been developed and used [4][5][6][7]. The process models-based methods do not generate spatially explicit predictions and often lead to a large amount of uncertainty for specific sites, partly because too many variables and input parameters are required to run the models and partly because different source data such as climate and soil data have very coarse spatial resolutions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The process models-based methods do not generate spatially explicit predictions and often lead to a large amount of uncertainty for specific sites, partly because too many variables and input parameters are required to run the models and partly because different source data such as climate and soil data have very coarse spatial resolutions [8][9][10]. In contrast, remote sensing-based approaches have become popular due to their unique characteristics in data collection and presentation; that is, multitemporal remote sensing images not only reveal spatial variability, spatial distributions, and patterns of forests but also provide the potential to estimate their changes over time [4][5][6][7]. A large number of research papers on biomass estimation using remote sensing data have been published in the past three decades, as summarized in previous literature review papers (e.g., [4,6,[11][12][13][14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%
“…Hyde et al (2006) compared the biomass estimation from Lidar, SAR/ InSAR (a radar satellite), and ETM+ and Quickbird (optical sensors of moderate and high spatial resolution, respectively) and found that Lidar was the best single sensor for estimating biomass. Its higher accuracy in estimating biomass compared with Landsat TM and high-resolution Quickbird is also supported by Lu et al (2012) and Gonzalez et al (2010). Other studies focused on identifying methods to integrate Lidar with optical remote sensing (aerial and satellite images) to improve biomass estimation, given that biomass is related not only to tree structure, but also to factors strictly dependent on vegetation type , and optical remote sensing can provide information on vegetation type.…”
Section: Sierra Nevada Adaptive Management Projectmentioning
confidence: 86%
“…Accurate measures and predictions of biomass are critical for estimating carbon storage on a stand and forest scale and also a global scale. Vegetation height metrics derived from Lidar are often used to predict biomass and have been found to provide accurate estimates of biomass even when forest density is high, because Lidar is not affected by the saturation problem associated with optical sensors, which can make moderate-density forests appear similar to high-density forests (Lu et al 2012). Hyde et al (2006) compared the biomass estimation from Lidar, SAR/ InSAR (a radar satellite), and ETM+ and Quickbird (optical sensors of moderate and high spatial resolution, respectively) and found that Lidar was the best single sensor for estimating biomass.…”
Section: Sierra Nevada Adaptive Management Projectmentioning
confidence: 99%
“…In the past several years, a few authors have been dealing with similar topics. In [21,22], an uncertainty analysis is performed to estimate forest carbon stock and biomass from satellite imagery and LiDAR data. The dominate sources of uncertainty are the variation of input sample plot data and data saturation problems related to optical sensors.…”
Section: Introductionmentioning
confidence: 99%